Mastitis in Ettawa Crossbred Goat (Pe) Caused by Staphylococcus Aureus: Epidemiology, Clinical Signs, Pathogenesis, Diagnosis and Control - Widodo Suwito; Indarjulianto S (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Mastitis in Ettawa crossbred goat is commonly found and caused economic loss. Staphylococcus aureus is one of bacteria caused clinical mastitis or subclinical mastitis in Ettawa crossbred goat. The aim of this review was to provide an overview of clinical and subclinical mastitis in the Ettawa crossbred goat caused by S. aureus from epidemiological aspect, clinical symptoms, pathogenesis, diagnosis, treatment, prevention and control. Mastitis should be eliminated because it lead to death for the goats and lambs. In addition, S. aureus has greater risk for contamination in milk because it produces heat-stable toxin. Isolation and identification bacteria with total of somatic cell counts are important as a reference to determine the actions to decrease the occurrence of mastitis. Some preventive measures for mastitis include clean milking, dipping the teats with a disinfectant and antibiotic treatment during dry lactation. Key words: Ettawa crossbred goat, mastitis, S. aureus, diagnosis, preventif